Corporate Social Responsibility (CSR) Perum Perhutani di Kecamatan Kalipuro, Kabupaten Banyuwangi - Ardiansyah, Vicky; Gianawati, Nur Dyah (University of Jember, 2015)
Abstract CSR (Corporate Social Responsibility) in Indonesia is the mandate of the legislation, namely, the Law No.25 of 2007 on TLN No.4274 LNNo.67 Investment and Law Number 40 of 2007 on Limited Liability Article 74 paragraph (1) of the company that runs its business activities in the field and / or related to the natural resources required to carry out its social and environmental responsibilities. Perum Perhutani is one of the state-owned enterprises that have implemented CSR. This research is focused on how to answer the problem formulation on CSR implementation Perhutani office in Forest Village Community Institution Rukun Makmur Kalipuro subdistrict in order to determine, describe and explain the implementation of the program. This study used qualitative research methods, descriptive research, data collection based on observations, interviews and documentation as well as the determination of informants using purposive sampling technique. Analysis of qualitative data, ie everything that is said informants, both written and verbal and real behavior were studied. Powered by the technique of triangulation validity sumberdata guide you in preparing the discussion. The results showed that the implementation of programs to improve the welfare of society as evidenced by an increase in revenues and an increase in knowledge about plants and institutional